Where Does Multinational Profit Go with Territorial Taxation? Evidence from the UK - Dominika Langenmayr; Li Liu (Center for Economic Studies and ifo Institute (CESifo), 2020)
In 2009, the United Kingdom abolished the taxation of profits earned abroad and introduced a territorial tax system. Under the territorial system, firms have strong incentives to shift profits abroad. Using a difference-in-differences research design, we show that profits of UK subsidiaries in low-tax countries increased after the reform compared to subsidiaries of non-UK multinationals in the same countries, by an average of 2.1 percentage points. The increase in profit shifting also leads to increases in measured productivity of the foreign affiliates of UK multinationals of between 5 and 9 percent.
Keywords: H25; H87; F23; 330; profit shifting; territorial tax system; multinational firms